Lithium isotopes in speleothems: Temperature-controlled variation in silicate weathering during glacial cycles - von Strandmann, P; Vaks, A; Bar-Matthews, M; Ayalon, A; Jacob, E; Henderson, G (Elsevier, 2017)
Terrestrial chemical weathering of silicate minerals is a fundamental component of the global cycle of carbon and other elements. Past changes in temperature, rainfall, ice cover, sea-level and physical erosion are thought to affect weathering but the relative impact of these controls through time remains poorly constrained. This problem could be addressed if the nature of past weathering could be constrained at individual sites. In this study, we investigate the use of speleothems as local recorders of the silicate weathering proxy, Li isotopes. We analysed δ7Li and [Li] in speleothems that formed during the past 200 ka in two well-studied Israeli caves (Soreq and Tzavoa), as well as in the overlying soils and rocks. Leaching and mass balance of these soils and rocks show that Li is dominantly sourced from weathering of the overlying aeolian silicate soils. Speleothem δ7Li values are ubiquitously higher during glacials (~23‰) than during interglacials (~10‰), implying more congruent silicate weathering during interglacials (where “congruent” means a high ratio of primary mineral dissolution to secondary mineral formation). These records provide information on the processes controlling weathering in Israel. Consideration of possible processes causing this change of weathering congruency indicates a primary role for temperature, with higher temperatures causing more congruent weathering (lower δ7Lispeleo). The strong relationship observed between speleothem d7Li and climate at these locations suggests that Li isotopes may be a powerful tool with which to understand the local controls on weathering at other sites, and could be used to assess the distribution of weathering changes accompanying climate change, such as that of Pleistocene glacial cycles.